The Collected Poems of John Ciardi - Ciardi, John, 1916-1986 (Book collections on Project MUSE., 1997)
In his biography of Ciardi, Edward Cifelli says this poet is one best remembered and understood as writing in a special class of American poets, including contemporaries like Robert Lowell, Elizabeth Bishop, Richard Wilbur, and Randall Jarrell. This collection finally demonstrates the scope and wealth of his contribution to that era. Further, it shows how, while always experimenting in form and meter and perfectly matching his structures to his subject matter, Ciardi resolutely held to an aesthetic that kept his poetry' free of the wavering fashions that dominated American poetry in the latter half of the twentieth century In The Collected Poems of John Ciardi, editor Edward Cifelli has gathered for us a "total poem" that is a powerful revelation of the career of a great American poet.